2015
DOI: 10.18267/j.pep.532
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Exchange Rate Exposure of Energy Firms: Evidence from Turkey

Abstract: Abstract:This study investigates the exchange rate exposure of Turkish energy fi rms from 2002 to 2010. We employed a regression model that is constructed by adding exchange rate and oil price factors to Fama-French Three Factor Model. Empirical results suggest that exchange rate risk appears to impact energy fi rms diversely. Among the 9 energy fi rms in our sample, only 2 fi rms seem to be exposed to exchange rate risk. These two energy fi rms appear to have larger open foreign currency positions and do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This finding also found out in Baum et al (2001), also Hidayati (2014) that say exchange rate affects profitability. Kandir et al (2015) also found out that exchange rate fluctuation also affect the financial capability of energy companies, eventhough the effect might vary. In transportation sector, the 1997 crisis in Indonesia, for example, the price of imported goods rose, people purchasing power declined, and transportation company revenue was not adequate enough to keep its financial ability (Abdulkadir, 2000).…”
Section: Research Hypothesismentioning
confidence: 97%
See 1 more Smart Citation
“…This finding also found out in Baum et al (2001), also Hidayati (2014) that say exchange rate affects profitability. Kandir et al (2015) also found out that exchange rate fluctuation also affect the financial capability of energy companies, eventhough the effect might vary. In transportation sector, the 1997 crisis in Indonesia, for example, the price of imported goods rose, people purchasing power declined, and transportation company revenue was not adequate enough to keep its financial ability (Abdulkadir, 2000).…”
Section: Research Hypothesismentioning
confidence: 97%
“…Baum et al (2001) studied the impact the long-term and short-term effect of currency value on profitability. Kandir et al (2015) studied the effect of exchange rate on energy companies in Turkey. Gawlak studied the profitability of electricity companies.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, social entrepreneurship is gaining momentum with the resource dependence theory (Preffer and Salancik, 1978) complementing the conditions of social entrepreneurship for CCS and CCU. Bricolage is primarily locally sourced that has high likelihood to curb exchange rate risk impact thermal energy firms diversely (Kandir et al, 2015).…”
Section: Deployability Of Bricolage For Optimal Resource Mobilizationmentioning
confidence: 99%
“…Despite the sector-specific factor, there is no direct study on oil price on the exchange rate exposure. A closer study on Turkey's energy sector looks at the impact of the exchange rate exposure on energy firms, but the study did not address the impact of oil price on the currency exposure (Kandir, Erismis, & Ozturk, 2015). Hence, there is a dearth of studies offered in respect to crude oil price and foreign currency exposure.…”
Section: Oil Prices and Foreign Exchange Exposurementioning
confidence: 99%